A SYSTEMATIC REVIEW: THE CURRENT STATUS OF CARBAPENEM RESISTANCE IN IRAQ - Sarah Ahmed Hasan; Waad Mahmood Raoof; Shwan kamal Rachid (Scholar Express Journals, 2022)
In this systematic review, we present the prevalence rates of the carbapenem resistance and carbapenemase genes of 11 articles reported in different regions of Iraq. The highest rates of carbapenem genes were blaOXA-48 (73.8%) followed by blaNDM-1 (67.27%), in Baghdad, in Waist also blaOXA48 (57.8%) followed by blaNDM-1 (50%) were the highest rates of carbapenem genes. While bla VIM (58.3%) followed by blaNDM-1,2(50%) were the highest rates of carbapenem genes, in Kurdistan region. In Babylon &Karbala, the prevalence of blaOXA-1 gene was 100% and in Al-Diwaniyah, the highest rate of carbapenem genes was blaGES(83.3%).
Keywords: Gram Negative; Carbapenemase Gene; Carbapenem Resistance; Iraq